The current status of the design of resin-bonded fixed partial dentures, splints and overcastings - Hiroshi Shimizu; Tomohiro Kawaguchi; Yutaka Takahashi (Elsevier, 2014)
This review article describes the current status of resin-bonded fixed partial denture, splint and overcasting design. Several such designs have been introduced through the years, but there is no typical standard yet for the design of anterior resin-bonded prostheses. On the other hand, the design of posterior resin-bonded prostheses has generally been a standard D-shaped structure. To splint abutment teeth, including pathological mobile teeth, the application of resin-bonded retainers with additional retentive structures is recommended. Although a conventional design for resin-bonded overcastings has not been established yet, it is usually easy to add mechanical structures. The problem in clinical practice is the esthetics of the retainers, although the key to solving this problem may be to apply tooth-colored material.